Implementation of the Value of Mutual Cooperation in the "Banjar" Contribution System as an Effort to Strengthen the Community Economy Based on SDGs 1 and 10 in Gelora Village - Septin Anggun Taranita; Muhamad Ali; Pahrudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
: Poverty and economic inequality remain challenges in rural development, particularly related to limited social protection and local institutional capacity. In the context of sustainable development, local culturally based social practices have the potential to contribute to strengthening the community economy. This study aims to analyze the implementation of the value of mutual cooperation in the Banjar contribution system and its role in strengthening the economy of the Gelora Village community within the framework of Sustainable Development Goals (SDGs) 1 and 10. The study used a qualitative approach with a case study design. Data were obtained through participatory observation and in-depth interviews with purposively selected Banjar administrators and members, then analyzed thematically through the stages of data condensation, data presentation, and conclusion drawing. The results show that the Banjar contribution system represents social capital built on trust, collective norms, and strong social networks. This system functions as an informal social protection mechanism and community-based economic redistribution that helps strengthen members' economic resilience and contributes to efforts to reduce vulnerability and inequality at the village level. These findings demonstrate that customary institutional practices are relevant in supporting an inclusive and sustainable development agenda